Mechanical Properties and Failure Mechanisms of Novel Resin-infused Thermoplastic and Conventional Thermoset 3D Fabric Composites - Shah, S.Z.H. (Springer Science and Business Media B.V., 2021)
This paper presents an extensive comparison of the mechanical properties and failure mechanisms of a recently developed thermoplastic (Elium Â®) 3D fabric-reinforced composite (3D-FRC) with the conventional thermoset (epoxy) 3D-FRC. Experiments involved tensile tests, compression tests, V-notch shear tests, and short beam shear tests for specimens produced through the vacuum-assisted resin infusion process in each case. These tests were used for the determination of in-plane elastic constants, failure strengths and for investigating the failure mechanisms. A micro-mechanical model validated against these experiments was used to predict the remaining orthotropic elastic constants.Â This work enhances our understanding of the mechanics of infusible thermoplastic 3D-FRC as a new class of emerging materials and provides useful data which substantiates that thisÂ unconventional thermoplastic resin is also easier to recycle, uses similar manufacturing processes and canÂ be aÂ suitable replacement for conventional thermoset resins. Â© 2021, The Author(s), under exclusive licence to Springer Nature B.V.